Living on Your Own Terms : what is real rebellion? - Osho (Life essentials, 2013)
The Osho Life Essentials series focuses on the most important questions in the life of the individual. Each volume contains timeless and always-contemporary investigations and discussions into questions vital to our personal search for meaning and purpose. Forty years after the rebellions of the 1960s a new generation is again in the streets to challenge and to rebel against outdated structures and values, focusing political and economic systems and their failings. But this generation has the opportunity and responsibility to move the development of human freedom to the next level. Living on Your Own Terms will support this new generation and is by far more radical and revolutionary than anything this planet has ever seen.